Differential Effects of Autophagy-Related 10 Protein on HCV Replication and Autophagy Flux Are Mediated by Its Cysteine44 and Cysteine135 - Zhang, Miao-Qing; Li, Jian-Rui; Peng, Zong-Gen; Zhang, Jing-Pu (Frontiers in Immunology, 2018)
Autophagy-related 10 (ATG10) is essential for autophagy since it promotes ATG5-ATG12 complex formation. Our previous study found that there are two isoforms of the ATG10 protein, ATG10 (a longer one) and ATG10S, which have identical sequences except an absence of a 36-amino acid fragment (peptide B) in ATG10S, yet exhibit distinct effects on HCV genome replication. Here, we report the existence of two amino acids, cysteine at residue 44 and 135 (Cys44 and Cys135, respectively), in ATG10 being related to differential effects of ATG10 on HCV replication and autophagy flux. Through a series of ATG10 mutation experiments and protein modeling prediction, we found that Cys44 was involved in the dual role of the two isoforms of ATG10 protein on HCV replication and autophagy flux, and that Cys135 plays similar roles as Cys44, but the disulfide bond of Cys44-Cys135 was not verified in the ATG10 protein. Further analyses by full HCV virion infection confirmed the roles of -SH of Cys44 and Cys135 on HCV replication. ATG10 with deleted or mutated Cys44 and/or Cys135 could activate expression of innate immunity-related genes, including il28a, irf-3, irf-7, and promote complete autophagy by driving autophagosomes to interact with lysosomes via IL28A-mediation. Subcellular localization assay and chromatin immunoprecipitation assay showed that ATG10 with the sulfydryl deletion or substitution of Cys44 and Cys135 could translocate into the nucleus and bind to promoter of IL28A gene; the results indicated that ATG10 with Cys44 and/or Cys135 absence might act as transcriptional factors to trigger the expression of anti-HCV immunological genes, too. In conclusion, our findings provide important information for understanding the differential roles on HCV replication and autophagy flux between ATG10 and ATG10S, and how the structure-function relationship of ATG10 transformed by a single -SH group loss on Cys44 and Cys135 in ATG10 protein, which may be a new target against HCV replication.